Innovations-Sustainability-Modernity-Openness Conference (ISMO’19) 2019
DOI: 10.3390/proceedings2019016034
|View full text |Cite
|
Sign up to set email alerts
|

The Possibilities of Paper Sludge Waste (PSw) Utilization in Cement Materials

Abstract: The paper production is developed throughout the world, therefore, more paper sludge waste (PSw) is accumulating. The aim of this work was to determine the properties of PSw burned at 900 °C and its impact on physical–mechanical properties of cementitious matrix and evaluate its usage/utilization possibilities in cementitious materials. For the implementation of the aim, cement-based specimens were prepared and their –mechanical properties were determined. Specimens from five compositions were formed, with 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
2
0
3
Order By: Relevance
“…Azrizal et al [ 22 ] investigated the physical, chemical, and reactive properties of ash developed from the PMS and concluded that the ash could be used for different products in the building industries such as brick, concrete, etc. Banevičienė et al [ 23 ] burned the PMS at 900 °C and its impact on the physical-mechanical properties of the cementitious matrix and evaluate its usage/utilization possibilities in cementitious materials. They prepared various specimens by varying the weight percentage of the PMS.…”
Section: Introductionmentioning
confidence: 99%
“…Azrizal et al [ 22 ] investigated the physical, chemical, and reactive properties of ash developed from the PMS and concluded that the ash could be used for different products in the building industries such as brick, concrete, etc. Banevičienė et al [ 23 ] burned the PMS at 900 °C and its impact on the physical-mechanical properties of the cementitious matrix and evaluate its usage/utilization possibilities in cementitious materials. They prepared various specimens by varying the weight percentage of the PMS.…”
Section: Introductionmentioning
confidence: 99%
“…Disertacijos tema paskelbti devyni straipsniai: keturi Clarivate Analytics Web of Science duomenų bazės leidiniuose, turinčiuose citavimo rodiklį (Malaiskiene et al, 2019a(Malaiskiene et al, , 2021Banevičienė et al, 2021Banevičienė et al, , 2022, trys Clarivate Analytics Web of Science duomenų bazės "Conference Proceedings" leidiniuose (Malaiskiene et al, 2019b(Malaiskiene et al, , 2019cBanevičienė & Malaiškienė, 2020), vienas -kitų tarptautinių duomenų bazių leidiniuose (Banevičienė et al, 2019), vienaskitame recenzuojamame mokslo leidinyje (Banevičienė et al, 2018)…”
Section: Darbo Rezultatų Aprobavimasunclassified
“…Taip pat aprašytas sukurtas tyrimo metodas portlandito išsiplovimui įvertinti. Skyriaus tematika paskelbtos penkios publikacijos (Banevičienė et al, 2018(Banevičienė et al, , 2019(Banevičienė et al, , 2021(Banevičienė et al, , 2022Malaiskiene et al, 2021).…”
Section: Cementiniam Rišikliui Modifikuoti Ir Vandeniui Laidžiam Beto...unclassified
See 2 more Smart Citations